2017
DOI: 10.1002/pbc.26517
|View full text |Cite
|
Sign up to set email alerts
|

Combating blood stream infections during induction chemotherapy in children with acute myeloid leukemia: Single center results in India

Abstract: Optimal management of infectious complication is the biggest challenge in children receiving chemotherapy for acute myeloid leukemia (AML). We have analyzed the data of children undergoing AML induction chemotherapy at our center from 2002 to 2016 and found that Gram-negative infections are more predominant when compared to the published literature. There also has been a surge in multidrug-resistant (MDR) infections over the last 4 years, which has increased the need for supportive care and escalated the cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…among Gram-negatives. 18,20 Outcome results were encouraging since only 2 of 224 BSI episodes were fatal showing a low mortality rate (0.9%). This rate is comparable, if not better, with recent reports estimating the mortality of BSI among children with cancer at 2% to 2.7%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…among Gram-negatives. 18,20 Outcome results were encouraging since only 2 of 224 BSI episodes were fatal showing a low mortality rate (0.9%). This rate is comparable, if not better, with recent reports estimating the mortality of BSI among children with cancer at 2% to 2.7%.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, in line with the previous literature, our study showed also that the predominant bacteria isolated in children with cancer were CoNS among the Gram-positive ones and E. coli and Pseudomonas spp. among Gram-negatives 18,20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, because of overcrowding and a lack of antibiotic stewardship in LMICs, there is a higher incidence of multidrug-resistant infection that requires the use of more antibiotics and increases the costs of supportive care. 6…”
Section: Introductionmentioning
confidence: 99%